Testing the Academic Information System Application of SDN 192 Salobongko with the Boundary Value Analysis Technique - Fitrah Eka Susilawati; Supriadi Supriadi; Hildayanti Hildayanti (Jurnal Literasi Digital, 2022)
Each software is developed with a series of structured stages based on user needs. These stages are formed from a framework that forms the basis of well-planned and controlled software development. Software testing is a stage that ensures that software development that has been developed is free from errors or errors before being distributed to users. This study aims to find errors in input by using black box testing with boundary value analysis techniques in SDN 192 Salobongko academic information system applications. From the results of the test cases performed, it shows that the test was successfully carried out. The findings in this study are that the testing of the academic information system application at SDN 192 Salobongko has shown successful test results based on the test case scenarios that have been designed.